2015
DOI: 10.1371/journal.pone.0133868
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation among Social Insect Colonies: Persistent Regional and Colony-Level Differences in Fire Ant Foraging Behavior

Abstract: Individuals vary within a species in many ecologically important ways, but the causes and consequences of such variation are often poorly understood. Foraging behavior is among the most profitable and risky activities in which organisms engage and is expected to be under strong selection. Among social insects there is evidence that within-colony variation in traits such as foraging behavior can increase colony fitness, but variation between colonies and the potential consequences of such variation are poorly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 81 publications
2
34
0
1
Order By: Relevance
“…A recent study on another invasive ant, the polygyne form of the red imported fire ant Solenopsis invicta, similarly showed high variability among experimental colonies, even when collected at a single site (Bockoven, Wilder, & Eubanks, 2015). The causes of such high variability remain unknown and could arise from a variety of factors including colony genetics, environmental factors and colony composition (reviewed in Jandt et al, 2014), and it is known that natural selection can act on such variation (Gordon, 2013;Jandt & Gordon, 2016).…”
Section: Behavioural Variation Along the Introduction Pathwaymentioning
confidence: 99%
“…A recent study on another invasive ant, the polygyne form of the red imported fire ant Solenopsis invicta, similarly showed high variability among experimental colonies, even when collected at a single site (Bockoven, Wilder, & Eubanks, 2015). The causes of such high variability remain unknown and could arise from a variety of factors including colony genetics, environmental factors and colony composition (reviewed in Jandt et al, 2014), and it is known that natural selection can act on such variation (Gordon, 2013;Jandt & Gordon, 2016).…”
Section: Behavioural Variation Along the Introduction Pathwaymentioning
confidence: 99%
“…Recent studies on acorn ants (genus Temnothorax ) have likewise found that variation in resource allocation (i.e., production of workers vs. reproductives) is linked to colony behavior and intraspecific competition in T. regatulus (Bengston, 2018; Bengston & Dornhaus, 2015; Bengston, Shin & Dornhaus, 2017). Similar associations appear to present in the related T. longispinosis (Segev, Burkert, Feldmeyer & Foitzik, 2017), and there is circumstantial evidence for similar associations in fire ants (Bockoven, Wilder & Eubanks, 2015) and gypsy ants too (Blight, Villalta, Cerda & Boulay, 2016). Yet, whether similar associations are present in other kinds of insect societies, for instance those with weaker reproductive division of labor, is unclear.…”
Section: Introductionmentioning
confidence: 53%
“…Studies in other species of social insect have recovered evidence for a colony-level pace-of-life (Reale, Garant, Humphries, Bergeron, Careau & Montiglio, 2010), where colonies can be placed along an axis of high-risk vs low-risk strategies that preferentially invest in reproductive output versus colony protection, respectively (Bengston, 2018; Bengston & Dornhaus, 2015; Bengston et al, 2017; Segev et al, 2017). More broadly, between-colony differences in collective aggressiveness and activity level have been associated with colony growth rates in several additional species (Blight et al, 2016; Bockoven et al, 2015). However, we recovered no evidence for such an association here.…”
Section: Discussionmentioning
confidence: 99%
“…However, in social insects, not only individuals can behave consistently, but also entire colonies can show stable characteristic behavioural differences (Bengston & Jandt, 2014; Jandt et al, 2014; Pinter‐Wollman, 2012; Wright et al, 2019) and hence can be said to have a collective or colony personality. This colonial level consistency might be important because in highly social organisms like eusocial insects, natural selection acts at the colony level (Blight, Albet Díaz‐Mariblanca, Cerdá, & Boulay, 2016; Bockoven, Wilder, & Eubanks, 2015; Hölldobler & Wilson, 1990; Modlmeier, Keiser, Wright, Lichtenstein, & Pruitt, 2015; Pinter‐Wollman, 2012; Pruitt & Modlmeier, 2015; Scharf, Modlmeier, Fries, Tirard, & Foitzik, 2012). For example, in Temnothorax nylanderi (Foerster, 1850), colonies show consistency in nest reconstruction, relocation after disturbance, removal of corpses and in their aggressive behaviour against the intruders (Scharf et al, 2012).…”
Section: Introductionmentioning
confidence: 99%